„Neue Leitbilder für den Fortschritt“ (LS 194). Ein Plädoyer für die Wiederentdeckung praktischer Weisheit als neues Leitbild in der Marktwirtschaft - Claudius Bachmann (Acta Universitatis Carolinae Theologica, 2016)
In the light of the far-reaching leadership failures and business scandals of the last decades, the question has often been raised of whether we are reaping the results of the practical application of abstract management theory which is actually counteracting a socially, environmentally, and economically sustainable market economy. In this sense, Pope Francis recently called for ‘new models of progress’ to reflect on ‘the meaning of the economy and its goals’ (LS 194). To answer these calls, I first provide an overview of the recent discourse in leadership and organizational studies that have critically scrutinized the established theories and models of mainstream business. Second, I draw on the Apostolic Exhortation Evangelii Gaudium and the Encyclical Laudato Si’ to derive the cornerstones of an ‘evangelizing approach’ to the guiding principles of management theory and practice suggested by Pope Francis. Third, to facilitate this renewal, I introduce the ancient idea of practical wisdom (prudence) which has recently enjoyed a remarkable renaissance in the literature and is considered as a new transformative paradigm for management theory and practice.